Isoxazolotacrines as non-toxic and selective butyrylcholinesterase inhibitors for Alzheimer's disease. (November 2014) - Cherif, Oussama; Allouche, Fatma; Chabchoub, Fakher; Chioua, Mourad; Soriano, Elena; Yañez, Matilde; Cacabelos, Ramón; Romero, Alejandro; López , Manuela G; Marco-Contelles, Jose
Background : Owing to the complex nature of Alzheimer's disease, there is a renewed and growing search for multitarget non-toxic tacrines as simple, easily available drugs in order to stop the progress and development of the disease.Results : This paper describes our preliminary results on the synthesis, in vitro biochemical evaluation and molecular modeling of isoxazolotacrines as potential drugs for the treatment of Alzheimer's disease. Novel 3-phenyl-5, 6, 7, 8-tetrahydroisoxazolo[5, 4- b ]quinolin-4-amine (OC41) is a promising, 31% less toxic than tacrine in HepG2 cells, and selective reversible human butyrylcholinesterase inhibitor (IC50 = 5.08 ± 1.12 µM), also showing good drug-like properties according to the absorption, Distribution, Metabolism, Excretion, Toxicity analysis.Conclusion: A new family of non-hepatotoxic permeable tacrine analogs, showing selective butyrylcholinesterase inhibition, have been discovered for the potential treatment of Alzheimer's disease.